DEVELOPMENT OF MANAGEMENT COMPETENCIES OF HEADS OF MEDICAL INSTITUTIONS AS A FACTOR OF STRENGTHENING SECURITY OF HEALTH OF POPULATION - Zapukhliak, Ivanna Bogdanivna; Romashko , Oleksandra (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2020)
Abstract. The article proves that one of the ways to improve medical care is to form a system of effective management of health care facilities.It is through the effectiveness of health workers that a high level of population health is achieved, which is the basis of socio-economic, scientific, cultural development of any society and is an important component of its social security. The aim of the article is to develop a profile of competencies of the head of a medical institution, identify the actual level of management competencies and formulate recommendations for the development of managerial competencies of heads of domestic health care facilities to strengthen public health.It is substantiated that in modern conditions, the ability of health care managers to establish cooperation with all stakeholders, apply a sustainable smart-approach to health care, introduce the latest technologies and advances in medicine, self-development and promote the development of other employees is important.All this requires the formation of new managerial qualities and competencies in the heads of health care institutions. Given this, it is not enough for the head of a medical institution to have only a high level of medical knowledge, it is also necessary to have elements of financial management, strategic planning and marketing, risk and conflict management, to have a high readiness for change. We believe that the development of managerial competencies of heads of medical institutions will contribute to effective management of health care facilities, which, in turn, will provide one of the most important components of social security - the health of the individual - the team - society.The domestic and foreign experience of forming the necessary managerial competencies in the heads of health care institutions is considered, which allowed systematizing the information and building an appropriate profile of competencies for domestic medical managers. Based on a survey on the level of mastery of managerial competencies by domestic physicians-managers, identified areas for improvement and substantiated the need for physicians to obtain management education using the concept of lifelong learning.